The Effectiveness “Guess What Game” to Teach English Vocabulary to the Eighth Grade Students of Junior High School Kartika Jaya of Palembang - Achmad Febriansyah (Universitas PGRI Palembang, 2018)
Abstract The main problem of this study was “Is it effective using guess what game to teach English vocabulary to the eighth grade students of Junior High School Kartika Jaya of Palembang?” The game focus on the word has relationship with action verbs. The objective of this study was to find out whether or not it was effective to use guess what game to teach English vocabulary to the eighth grade students of Junior High School Kartika Jaya of Palembang. This study used the true experimental method. The written tests were used to collect the data. The data were analyzed through the independent t-test. The population of this study was all the eighth grade students of Junior High School Kartika Jaya of Palembang in the academic year of 2017/2018. The sample students of this study were taken from the population by using cluster random sampling method. Based on the study, it was found that “guess what game” was effective in teaching English vocabulary to the eighth grade students of Junior High School Kartika Jaya of Palembang. The average score of the students in the post-test of the experimental group was 87.2. On the other hand, average score in the post-test of the control group was 85.6. The students’ scores and the result of the independent t-test computation was 2.333 in the critical value at 0.05 significance level was 2.000 and t-obtained Null Hypothesis (Ho) was rejected and Alternative Hypothesis (Ha) was accepted. It means, using guess what games to the eighth grade students of Junior High School Kartika Jaya of Palembang was effective.